2018
DOI: 10.1101/419226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Redundant and cryptic enhancer activities of the Drosophilayellowgene

Abstract: cis-regulatory sequences known as enhancers play a key role in regulating gene expression. Evolutionary changes in these DNA sequences contribute to phenotypic evolution. The Drosophila yellow gene, which is required for pigmentation, has emerged as a model system for understanding how cis-regulatory sequences evolve, providing some of the most detailed insights available into how activities of orthologous enhancers have diverged between species. Here, we examine the evolution of yellow cis-regulatory sequence… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…The number of enhancers that contacted a gene was a positive predictor of expression, but did not reach statistical significance (ß ENH : 2.51 +/−2.06). It is well known that enhancers are often cryptic and redundant (42, 43), which supports our finding that genes with at least one enhancer association displayed significantly higher expression in Figure 3C, but that the presence of additional enhancers was not associated with a further increase in expression. We cannot rule out that unannotated CRE are functional regulators of expression, as non-STARR functional ATAC-Seq peaks demonstrate significant positive influence on expression of target genes ( 3E) .…”
Section: Resultssupporting
confidence: 92%
“…The number of enhancers that contacted a gene was a positive predictor of expression, but did not reach statistical significance (ß ENH : 2.51 +/−2.06). It is well known that enhancers are often cryptic and redundant (42, 43), which supports our finding that genes with at least one enhancer association displayed significantly higher expression in Figure 3C, but that the presence of additional enhancers was not associated with a further increase in expression. We cannot rule out that unannotated CRE are functional regulators of expression, as non-STARR functional ATAC-Seq peaks demonstrate significant positive influence on expression of target genes ( 3E) .…”
Section: Resultssupporting
confidence: 92%
“…Similarly, Omb (Brisson et al 2004) and Wingless (Wg, a ligand for a signal transduction pathway) (Werner et al 2010; Koshikawa et al 2015) have also been shown to influence expression of at least one pigment synthesis gene (Figure 1), although questions remain about the precise molecular mechanisms by which they do so. Additional transcription factors with effects on abdominal pigmentation in Drosophila melanogaster have been identified in recent RNAi screens (Kalay 2012; Rogers et al 2013a), but the ways in which they alter expression of pigment synthesis genes remains unknown. Elucidating the structure and complexity of the gene network regulating expression of pigment synthesis genes (and hence pigmentation) remains one of the biggest challenges for understanding the development and evolution of Drosophila pigmentation within and between species.…”
Section: Development Of Drosophila Pigmentationmentioning
confidence: 99%
“…This definition takes the preserved distance of regulatory information to the core promoter into account as well as the local genomic context at the yellow locus. We submit that this approach is more informative than testing the sole sufficiency of an isolated segment, as is classically done (21). These cores can logically be visualized in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…blade enhancer (referred to as "wing" in other publications) and the recently evolved spot enhancer (6,7,(17)(18)(19)(20)(21). In D. biarmipes, both activities map within 6 kb upstream of y transcription start site (6) (y 5′ region) ( Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation